2019
DOI: 10.1002/mp.13396
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a prototype rapid kilovoltage x‐ray image guidance system designed for a ring shape radiation therapy unit

Abstract: Purpose This study aims to characterize the performance of a prototype rapid kilovoltage (kV) x‐ray image guidance system onboard the newly released Halcyon 2.0 linear accelerator (Varian Medical Systems, Palo Alto, CA) by use of conventional and innovatively designed testing procedures. Methods Basic imaging system performance tests and radiation dose measurements were performed for all eleven kV‐cone beam computed tomography (CBCT) imaging protocols available on a preclinical Halcyon 2.0 LINAC. Both conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 18 publications
2
99
0
Order By: Relevance
“…Due to the kVCBCT’s lower imaging dose and fast acquisition time (as low as 16.7 s), we anticipate its wide usage. Image acquisition for Halcyon thus is faster than TrueBeam due to the fourfold increase in gantry rotation speed . In conclusion, treatment delivery times should be comparable between both treatment machines given that patient setup times are significantly longer than beam on times for this type of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the kVCBCT’s lower imaging dose and fast acquisition time (as low as 16.7 s), we anticipate its wide usage. Image acquisition for Halcyon thus is faster than TrueBeam due to the fourfold increase in gantry rotation speed . In conclusion, treatment delivery times should be comparable between both treatment machines given that patient setup times are significantly longer than beam on times for this type of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum dose rate for a flattened 6 MV or 10 MV is 600 MU/min at isocenter for TrueBeam and 800 MU/min at isocenter for the 6FFF beam provided on the Halcyon LINAC. Halcyon was designed to address the global need for access to radiation therapy with integrated imaging guidance, improved clinical efficiency, and shorter installation and commissioning time as well as operational demands . However, the jawless design and unflattened beam provide some challenges when creating breast 3D plans with the FiF techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Our test systems, in common with some systems currently available, only offer megavoltage imaging. The Halcyon is designed, however, to facilitate the addition of kV imaging with the imaging beamline perpendicular to the treatment beamline (the same as with most other medical linacs) – at the time of writing, this has just become commercially available and has been characterized by Cai et al Kilovoltage imaging may allow a means to facilitate equipment setup during commissioning – although we found that the MV imaging was sufficient, and may be preferable as it uses the treatment beam line. Results from other commissioning tests are provided in the supplemental material (Data & Appendix ).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of publications that either evaluate the operation of the Halcyon or provide recommendations on its clinical use . A recent publication provided a risk assessment of Halcyon acceptance testing and commissioning processes using the TG‐100 methodology .…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of publications that either evaluate the operation of the Halcyon or provide recommendations on its clinical use. [1][2][3][4][5][6][7][8][9][10][11] A recent publication provided a risk assessment of Halcyon acceptance testing and commissioning processes using the TG-100 methodology. 12 In that work, 142 failure modes were identified with the top risk priority number (RPN) values ranging from 85.5 to 95.0 for the acceptance testing and commissioning, respectively.…”
Section: Introductionmentioning
confidence: 99%